Econmoy of fascination: Dubai and Las Vegas as examples of themed urban landscapes - Schmid, Heiko (ERDKUNDE, 2006)
Large investments in the real estate and tourism sector, as well as rising numbers of tourists and immigrants, have led to a sustained boom in Dubai and Las Vegas. At the same time, and against the background of an urban governance and the transfer of competences to private and semi-state actors in both metropolises, a brisk urban transformation has been embarked upon, with the creation of countless entertainment, shopping, and artificial worlds. This development is primarily characterised by the theming of everyday life, but above all an Economy of Fascination. The casino and hotel landscapes simulating various scenes from Ancient Rome to modern New York, artificial islands in the shapes of palm trees or whole world maps, as well as other superlatives in the form of themed shopping malls and sports arenas, are the most visible results of these rapid changes. Dubai and Las Vegas are not only the first in a general trend towards commercialisation and entertainment orientation in the age of economic and cultural globalisation, but they are also quite extreme examples of post-modern urban development. This paper develops guidelines for a research perspective called Economy of Fascination and turns to Dubai and Las Vegas to exemplify the approach. An analytical understanding first builds on general trends and development lines against the backdrop of urban governance, entertainment orientation, and commercialisation. They form the starting point for an analysis of the mechanisms of attention and fascination, which are considered to be the main aspects of an Economy of Fascination. In order to understand these mechanisms the economic interrelations, protagonists, and processes of action are of particular importance. Following the theory of structuration by ANTHONY GIDDENS (1984) and the social geography of everyday regionalisations by BENNO WERLEN (1995, 1997), an action theory approach lends itself as a basic perspective. At the same time though, the economically-orientated attempts to gain attention are put into practice using post-modern aesthetics and symbolic ascriptions. Formulating an Economy of Fascination as a research perspective thus calls for an extension of the action theory to include semiotic approaches.